Developing Multimodal Teaching Materials for Persuasive Writing within a Genre-Based Pedagogy - Ariefin, Muhammad; Sintowati Rini Utami; Miftahulkhairah Anwar (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study aim to develop and validate multimodal teaching materials integrated with a Genre-Based Approach to strengthen junior-secondary persuasive writing in bahasa Indonesian class. Motivated by gaps in monomodal textbooks and inconsistent enactment of genre pedagogy, we followed a Research and Development (R&D) design using the ADDIE model. The digital e-module operationalizes Building Knowledge of the Field, Modelling, Joint Construction, and Independent Construction, and coordinates text, images, layout, and audio so verbal and visual resources support the same persuasive functions. A limited classroom trial with Grade VIII students (n = 39) examined feasibility and learning movement. Evaluation combined expert validation of content  and material, language and readability, and media and design, teacher and student user-response indices, and curriculum-aligned pre and posttests. Analyses were descriptive. Expert validation yielded 92.76 %, categorized as very feasible. Teacher reported 93.35 %, also very feasible. Students reported 82.75 %, feasible. Mean scores increased from 65.22 % on the pretest to 85.74 % on the posttest, a gain of 20.51 points, with an average normalized gain of 0.61 indicating medium effectiveness. Findings suggest that explicit genre scaffolding coupled with principled multimodal orchestration is classroom-ready and educationally valuable. Recommendations include clearer stepwise drafting prompts, compact lexis banks for stance, and stronger intermodal signalling.